Prevailing Insects And Mite Pests Of Brinjal And Their Natural Enemies At Jashore In Bangladesh - Ghosh, A; Biswas, GC; Paul, A; Tandra, AB (Bangladesh Journal of Agricultural Research, 2023)
Abstract not available Bangladesh J. Agril. Res. 46(1): 117-121, March 2021